2015
DOI: 10.3174/ajnr.a4458
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-Enhanced MR Imaging in Head and Neck Cancer: Techniques and Clinical Applications

Abstract: SUMMARY:In the past decade, dynamic contrast-enhanced MR imaging has had an increasing role in assessing the microvascular characteristics of various tumors, including head and neck cancer. Dynamic contrast-enhanced MR imaging allows noninvasive assessment of permeability and blood flow, both important features of tumor hypoxia, which is a marker for treatment resistance for head and neck cancer. Dynamic contrast-enhanced MR imaging has the potential to identify early locoregional recurrence, differentiate met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 73 publications
0
117
1
2
Order By: Relevance
“…We found no difference in iAUC 60 between ONBs and SCCs, revealing that both exhibit similar tumor blood flow. Interestingly, the mean V e value of ONBs was significantly lower than that of SCCs, indicating that the volume of the EES in ONBs was lower than that of SCCs . Previous studies demonstrated that higher V e values were considered to be associated with a rich stroma, which is composed of fibroblasts, endothelium, and extracellular matrix components .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…We found no difference in iAUC 60 between ONBs and SCCs, revealing that both exhibit similar tumor blood flow. Interestingly, the mean V e value of ONBs was significantly lower than that of SCCs, indicating that the volume of the EES in ONBs was lower than that of SCCs . Previous studies demonstrated that higher V e values were considered to be associated with a rich stroma, which is composed of fibroblasts, endothelium, and extracellular matrix components .…”
Section: Discussionmentioning
confidence: 85%
“…Quantitative DCE‐MRI with a pharmacokinetic model proposed by Tofts and Kermode is a useful technique to evaluate tumor permeability and angiogenesis and to differentiate various types of tumors. In vivo measurements of K trans , K ep , V e , and iAUC 60 have been shown to correlate with tumor vascularity and serve as an indicator for differential diagnosis of tumors in the head and neck region . K trans is a rate constant, qualifying the contrast agent diffusion from the blood plasma through the capillary wall into the EES, whereas K ep is a reverse rate constant of the contrast agent diffusion from the EES back to the plasma .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DCE-MRI has been used for prediction of treatment response [64] by measuring blood flow–related parameters such as perfusion, permeability, or vascular volume [6567]. Because the efficacy of chemoradiation therapy relies on effective delivery of therapeutic agents and oxygen to the tumor, the information on tumor vessels and related tumor microenvironment measured by DCE-MRI can provide critical information on selection of the most effective treatment strategy [50, 68, 69].…”
Section: Treatment Response Monitoring and Predictionmentioning
confidence: 99%
“…However, K trans emerged as a marker for tumor hypoxia indicating poorer survival or poorer treatment response and has the potential to be a useful biomarker to guide treatment in head & neck squamous cell cancer [32,34,35]. It may also have the potential to identify early locoregional recurrence and differentiate metastatic lymph nodes from normal nodes [36]. DCE MRI may differentiate paraganglioma with high peak enhancement, SER, and short TME from schwannoma which shows a relatively low peak enhancement and SER with a longer TME [37].…”
Section: Vessels and Perfusion: 3d-tof Twist/tricks Angiography Dcementioning
confidence: 99%